Relief for the environment? The importance of an increasingly unimportant industrial sector - Martin Gassebner; Noel Gaston; Michael Lamla (ETH Zurich, KOF Swiss Economic Institute, 2006)
Deindustrialisation, stagnant real incomes of production workers and increasing inequality are latter-day features of many economies. It's common to assume that such developments pressure policy-makers to relax environmental standards. However, when heavily polluting industries become less important economically, their political importance also tends to diminish. Consequently, a regulator may increase the stringency of environmental policies. Like some other studies, we find that declining industrial employment translates into stricter environmental standards. In contrast to previous studies, but consistent with our argument, we find that greater income inequality is associated with policies that promote a cleaner environment.
Keywords: Q58; P16; J31; C23; 330; Environmental regulations; deindustrialisation; income inequality; extreme bounds analysis; Deindustrialisierung; Industrieller Strukturwandel; Umweltschutz; Umweltpolitik; Einkommensverteilung; Panel